Climate change during the Triassic and Jurassic. (24th November 2017) - Harris, Rhys; McCall, Robert; Randall, Oliver; Bin Tawang, Muhammad Hafiz; Williams, Rhys; Fairman, Jonathan G.; Schultz, David M.
Abstract : The transition from the Triassic to Jurassic is associated with dramatic changes in Earth's climate. Pangaea was breaking up as North America rifted away from Africa, the Central Atlantic Magmatic Province erupted, and the concentration of atmospheric carbon dioxide increased dramatically. This article summarises the changes in Earth's climate associated with this transition, including a discussion of the various impacts of the increased carbon dioxide on the Earth system, the question of whether the wet episode in the Carnian was a global or regional event, the formation of bauxite deposits, and how dinosaur distributions changed over time. Palaeoclimate model simulations reveal the spatial changes in climate between the Triassic and Jurassic, illustrating the subtropics becoming slightly cooler and wetter despite the warming trend for the Earth's average temperature.